Evolving Nurse Education According to Future Needs - Solgajová Andrea; Zrubcová Dana; Ľuboslava Pavelová; Sollár Tomáš; Elonen Imane; Salminen Leena (Turun yliopisto, 2025)
In designing a curriculum for nurse education, it is important to be able to integrate knowledge about critical issues and important topics into nursing education as well as utilising pedagogically relevant methods to deliver the education. Nurse educators when educating future nurses or other healthcare professionals should be able to respond to the changing needs in the healthcare system. Nurse educators should have competencies in management, leadership, and advocacy along with the skills necessary for designing, implementing, evaluating the management of curricula. Furthermore, subject competence as well as pedagogical competence remain important, despite new demands on these competences as a consequence of societal and health care changes. Various measures (for example: The Health and Social Care Educator’s Competence – HeSoEduCo; Mikkonen et al., 2020) may be used in self-evaluation by nurse educators to evaluate their competence. In this Chapter we focus on the content of critical issues in future nursing education both from the perspective of the pedagogy and the future health service requirements, and the competencies required to adapt to the potential changes that future may bring.
Empowering Future Nurse Educators